Human resources management in small and medium enterprises - Ceranic, Slobodan; Popovic , Blaženka (Applied Studies in Agribusiness and Commerce, 2009)
Development of small and medium enterprises (SME) represents primary goal of every modern economy. It is complex challenge which includes great number of directly concerned parties in every sector of the state and economy. SME stimulate private ownership and entrepreneurship. Their characteristic is that they are flexible and can easily adjust to changes in supply and demand on the market. At the same time they open possibilities for increase of employment, promote diversification of economical activities, support sustainable growth and give significant contribution to export, trade and increase the competitiveness of the entire economy. Importance of SME for economy is undisputable. All research show that globally, more than 90% of all business activities are realized by SME. SMEs employ two thirds of total labor of European Union. Approaching to European Union presumes harmonization of the systematic environment and improvement of the climate of entrepreneurship, private initiative, development of SME. This determination has strongpoint in current world processes that prefer the development of SME, utilizing their profit efficiency and established advantages relating to the adaptability of small business to dynamic changes in economy. Problem of Human resources management is very sensitive issue in SMEs. Namely, in big companies there are entire teams of agencies or consultants are hired for selection and education of new employees, whereas in SMEs this work is done by owner or manager. Therefore, in this paper several facts were pointed out which need to be considered in selection of new employees, since every mistake in this activity can cause far-reaching consequences on functioning of SME.